Determinan Tingkat Kemandirian Keuangan Daerah pada kabupaten/Kota di Provinsi Sumatera Selatan - Verawaty Verawaty; Septiani Fransisca; Richa Rahmawati (MBIA, 2017)
This research was aimed to test the effect of local own source revenue (PAD), general allocation fund, special allocation of fund, revenue-sharing fund, other legitimate income as the determinants to the level of local financial independence in South Sumatra. Data was obtained from the budget realization report from 2013-2014. Determination of samples was 17 local governments in South Sumatra. The data were secondary data obtained from Central Agency on Statistics (BPS). The results showed that PAD had significant positive effect on the level of local financial independence. The general allocation fund, revenue-sharing fund, and other legitimate income had significant negative effect on the level of local financial independence. The special allocation fund got the negative effect but not significant on the level of local financial independence.